Lower risk of stroke after alcohol abstinence in patients with incident atrial fibrillation: a nationwide population-based cohort study. (14th October 2021) - Lee, S R; Choi, E K; Jung, J H; Han, K D; Oh, S; Lip, G Y H
Abstract: Background: In a recent study, alcohol abstinence reduced the atrial fibrillation (AF) recurrence in patients with AF. However, the relationship between alcohol consumption and incident stroke in patients with AF per se remains unclear. Purpose: To evaluate the association between alcohol consumption status (and its changes) after newly diagnosed AF and the risk of ischaemic stroke. Methods: Using the Korean nationwide claims and health examination database, we included subjects who were newly diagnosed with AF between 2010 and 2016. Patients were categorized into three groups according to the status of alcohol consumption before and after AF diagnosis: non-drinkers; abstainers from alcohol after AF diagnosis; and current drinkers. The primary outcome was incident ischaemic stroke during follow-up. Results: Among a total of 97, 869 newly diagnosed AF patients, 51% were non-drinkers, 13% were abstainers, and 36% were current drinkers. After inverse probability of treatment weighting, baseline characteristics of three groups were well-balanced. Compared to current drinkers, abstainers and non-drinkers were associated with a lower risk of ischaemic stroke (hazard ratio [HR] 0.86, 95% confidence interval [CI] 0.77–0.96 for abstainers and HR 0.75, 95% CI 0.70–0.81 for non-drinkers, respectively). Amongst current drinkers, there was a dose-response relationship between the amount of alcohol consumption and the risk of ischaemic stroke. Conclusion: Current alcohol consumption was associated with an increased risk of ischaemic stroke in patients with newly diagnosed AF, and alcohol abstinence after AF diagnosis could reduce the risk of ischaemic stroke. Lifestyle intervention, including attention to alcohol consumption, should be encouraged as a part of a comprehensive approach to AF management to improve clinical outcomes. Funding Acknowledgement: Type of funding sources: None.